Methodological Tools for Assessing the Effectiveness of Implementation of the State Social and Economic Development Policy of Russia's Regions - Provorova, Anna; Gubina, Ol’ga; Smirennikova, Elena; Karmakulova, Anna; Voronina, Lyudmila (Economic and social changes, 2015)
The article considers the issues of improvement of methodological support in assessing the effectiveness of the state social and economic policy in relation to Russia’s northern regions. It provides a brief analysis of methodological approaches and mechanisms to assess the policies based on the function of the area of assessment, the object, subject and target of assessment, and depending on the methods of estimation. The authors point out the absence of a common approach to interpretation of the notions of “effectiveness” and “performance efficiency” of a policy, this fact leads to ambiguity and complexity of assessment. The methodological tools proposed by the authors for assessing the implementation of the policy include key principles and an algorithm. Assessment of policy effectiveness using the proposed tools includes socio-economic, environmental and institutional components. The socio-economic component involves evaluation of the goals and objectives of the policy with regard to Russia’s northern regions on the basis of qualitative and quantitative indicators. The environmental component involves consideration of the impact of territorial conditions on the achievement of goals and objectives. The institutional component includes assessment of the quality of regional state programs. The advantage of this set of methodological tools lies in the fact that it takes into consideration the regional and northern specifics in the policy target-setting, and provides for a comprehensive assessment. This makes it possible to develop specific recommendations for the regulation of various spheres of socio-economic development of Russia’s northern regions, and to identify reasons for failures in achieving the set goals and objectives